The Role Of Good Corporate Governance In Improving Company Financial Performance - Pani Gunawan Pratama; Dina Adelia; Arwenda Sardi Malau; Zul Sahyani Limbong; Fitri Yani Panggabean (Sean Institute, 2025)
This study examines the role of Good Corporate Governance (GCG) in improving company financial performance. Corporate governance is a crucial mechanism that ensures transparency, accountability, and efficiency in business operations, ultimately enhancing financial stability and investor confidence. Effective governance practices help mitigate risks, optimize decision-making, and strengthen a company’s competitive position in the market. Using a quantitative approach, this research analyzes the relationship between corporate governance indicators such as board structure, ownership concentration, audit committee effectiveness, and transparency and financial performance, measured through Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS). Data from publicly listed companies is analysed using multiple regression analysis to determine the significance of corporate governance in shaping financial outcomes. The findings indicate that strong corporate governance positively influences financial performance, with well-structured boards, independent audit committees, and high transparency levels contributing to improved profitability and financial stability. Companies with effective governance mechanisms tend to attract more investors, reduce financial risks, and achieve sustainable growth. This study provides valuable insights for corporate executives, investors, and policymakers, emphasizing the need for continuous improvements in corporate governance frameworks to enhance financial performance and long-term business success.